Discussion of the paper 'A general framework for functional regression modelling'. (February 2017) - Bai, Jiawei; Ivanescu, Andrada; Crainiceanu, Ciprian M.
Abstract: This discussion provides our reaction to the article by Greven and Scheipl. It contains an overview of their article and a description of the many areas of research that remain open and could benefit from further methodological and computational development.